On the application of approximation of the central manifold of a stationary point to one critical case - Nakonechna, S. O.; Наконечна, С. О. (Institute of Mathematics, NAS of Ukraine, 1998)
We establish conditions under which a central manifold can be replaced by its approximation in the reduction principle for ordinary differential equations in a critical case of one zero root.